Estudo das propriedades eletrônicas e estruturais da heterojunção dos nanotubos de nitreto de boro e nitreto de alumínio - Thesing, Leandro Antonio (2007)
In this work we present the study of the electronic and structural properties of the heterojunction formed by (10,0) zig-zag nanotubes of aluminum nitride (AlN) and boron nitride (BN). To simulate the system, we use periodic boundary conditions and an unit cell containing 160 atoms, 80 in the AlN nanotube and 80 in the BN nanotube. The calculations were performed using a first principles approach within the Density Functional Theory. The generalized gradient approximation was employed to treat the exchange and correlation functional. Due to the difference of 2.075 Åbetween the average diameters of the (10,0) AlN and BN nanotubes, a structural rearrangement takes place in the layers near the nanotube junctions, in the heterojunction. The zig-zag configuration of both nanotubes gives rise to two different junction. One of them contains bonds between the Al atoms in the AlN nanotube and the N atoms in te BN nanotube, whereas the other contains bonds between the N atoms in the AlN nanotube and the B atoms in the BN nanotube. A charge concentration of opposite signs is determined on the two different junctions, resulting in a electric dipole of 6 × 10−3 Debye along the nanotube axis. The heterojunction presents an energy gap of 2.5 eV, lower than those for the isolated AlN (3.2 eV) and BN (4.1 eV) nanotubes, in the density functional theory level. The formation of the heterojunction is seen to be an endothermic process, requiring 0.54 eV per chemical bond at the junctions. The band offset is determined to be of the type II, staggered, with the top of the valence band on the BN nanotube being 0.26 eV above in energy than the top of the valence band on the AlN nanotube.